Inovasi Minuman Sehat Berbasis Whey dan Sari Buah Tropis - Fauzan Rahmat Pradana; Chayrul Anwar; Nita Fridayani; Hafizh Abdul Aziz; Atqiya Nur’ Assyfa (Asian Journal of Innovation and Entrepreneurship, 2017)
Highly national demand for cheese impacts on the increase of whey. Whey in Indonesia is still considered as waste.Thought previous studies show that whey has many benefits such as maintaining immunity and providing minerals and amino acids. Liquid whey based beverage products in Indonesia are still underdeveloped. Wello is the first whey-liquid based beverage enriched with tropical fruits in Indonesia, offering unique flavors. The main raw materials used are liquid whey and tropical fruit juice with citric acid additives, sodium bicarbonate and sugar. Wello is made through pasteurization and packed in a bottle of 250 mL. Wello flavor variants available are sweet mango, mango sour and soursop. The product is targeted to children, adults and the elderly, offered at the price of Rp. 10.000,00. Promotions are made directly and through social media, leaflets, posters, banners and bazaars. The cooperation with commercial cheese company, Trie's Cheese has been initiated. Until today the sale has reached 146 bottles with a turnover of Rp 1.405.000,-. The business feasibility analysis shows the R / C ratio of 1.81 and the payback period of 4.5 months. Applying for halal certification, establishing cooperation with convenience stores, and building outlets are going tobe carried out to increase Wello commercialization, especially in Jabodetabek. Â